Does Public Sector Outsourcing Decrease Public Employment? Empirical Evidence from OECD Countries - Niklas Potrafke (Center for Economic Studies and ifo Institute (CESifo), 2018)
I examine the extent to which public sector outsourcing relates to public employment in OECD countries. I use new panel data on public sector outsourcing. The sample includes 26 countries over the period 2009-2015. Contrary to common expectations, the results do not suggest that public sector outsourcing expenditure was negatively related to public employment in the full sample. The relation between public sector outsourcing and public employment, however, does vary across countries. If anything, the growth in public sector outsourcing in period t-1 was positively correlated with the growth in public employment in period t. When public sector outsourcing gives rise to regrouping public employees but not reducing public employment, outsourcing may even increase inefficiencies in the public sector.
Keywords: L33; J45; P16; C23; 330; public employment; public sector outsourcing; OECD countries; economic policy-making; panel data